Kualitas Soal Penilaian Akhir Semester (PAS) Semester Ganjil Tahun Pelajaran 2020/2021 Pada Mata Pelajaran Kimia Kelas X SMK Se-Kota Palangka Raya - Rahmi Kuni Handayani; Suandi Sidauruk; Abdul Hadjranul Fatah (Jurnal Ilmiah Kanderang Tingang, 2023)
The goal of this research is to describe the quality of the End of Semester Assessment (PAS) questions for chemistry subjects in class X odd semester of SMK throughout the city of Palangka Raya for the 2020/2021 Academic Year. This research included descriptive research, with researchon questions and student answer sheets at odd end-of-semester assessments. The data collection technique of this study is the documentation method. Data analysis techniques use the help of the SPSS version 26 program. The results showed that the results of the logical review analysis obtained a good level of conformity of questions with basic competencies with a percentage of 21.90%. The suitability of the questions reviewed from the material aspect with a percentage of 93.88%, from the construction aspect the percentage of conformity of the questions was 90.81%, from the aspect of language the suitability of the questions obtained a percentage of 100%. The quality of the PAS question qualitatively (empirical review) shows that: the results of the analysis of the validity of the items about the P-Value Index 0.34 criteria are sufficient (20%-60%), the results of the analysis of the average reliability of the questions are the Cron'bach alpha r11 value< 0.70, namely at a value of 0.494 with sufficient criteria, the results of the analysis of the differentiating power of the questions are accepted (19%), the questions are rejected (26%), the questions are corrected (35%), and the questions are good (20%). Meanwhile, the results of the analysis of the difficulty level of questions with easy criteria (15.83%), questions with medium criteria (40.08%), and questions with difficult criteria (42.92%) and the results of the analysis of extractivity of the distractor (deceiving) quality of the category questions were very good with an average percentage of 81.38%.